2010
DOI: 10.5216/pat.v40i4.7266
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade De Farelos De Arroz Cru, Extrusado E Parboilizado

Abstract: básico apresentam maior percentual de pobreza e, consequentemente, graves deficiências nutricionais, que poderiam ser minimizadas pela utilização de subprodutos do arroz, como o farelo. No Brasil, o número de pessoas subnutridas, de 2001 a 2003, ultrapassou 14 milhões, aproximadamente 8% da população (FAOSTAT 2006).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 12 publications
0
9
1
10
Order By: Relevance
“…The protein content of the grape marc flour was close to Ferreira (2010) study which found 14.65% (w.b.). In the parboiled rice bran, Lacerda et al (2010) found higher values than this study, 17.17% (w.b.). In relation to the mineral content of grape marc flour, this by-product presented ash quantities consistent with other studies reported in the literature, such as Ferreira (2010) who found 7.36% (w.b.)…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…The protein content of the grape marc flour was close to Ferreira (2010) study which found 14.65% (w.b.). In the parboiled rice bran, Lacerda et al (2010) found higher values than this study, 17.17% (w.b.). In relation to the mineral content of grape marc flour, this by-product presented ash quantities consistent with other studies reported in the literature, such as Ferreira (2010) who found 7.36% (w.b.)…”
Section: Resultscontrasting
confidence: 81%
“…The lipid content in grape seeds depends on the used variety, although the usual range is 10 to 16% of dry weight (LUQUE-RODRIGUEZ et al, 2005). For rice bran, the value found by Lacerda et al (2010) was in the range of 10 to 23% (w.b. ), values consistent with the present study.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Higher values of chrome a* (above 2.6) were observed at temperatures above 76.7°C and moisture below 16.9 g.100g -1 ( Figure 3C). According to Lacerda et al (2010), the Maillard Figure 4. Graphic diagram of desirability aiming to obtain snacks with physical properties required for a product with commercial potential, depending on moisture and extrusion temperature during processing.…”
Section: Resultsmentioning
confidence: 99%
“…O farelo e a quirera (Tabela 2), possuem alto teor de carboidratos (89,7 e 69,1%, respectivamente) e baixo teor de proteína bruta (10,95 e 8,97%, respectivamente), caracterizando-os como alimentos energéticos. Estes ingredientes são considerados como tendo potencial para utilização em rações de animais (Lacerda et al, 2010).…”
Section: Resultsunclassified